Logbook of the whaling ship Constitution - Constitution (Ship)
Logbook (1840 May 10-1842 April 17; 125 pages) kept aboard the whaling ship Constitution, sailing mainly off the coast of Peru, with entries relating to weather and sea conditions, the sighting and killing of whales, and whale oil extraction.
Logbook belonging to a whaler from Nantucket, Mass.
Collection material in English.
Keywords: Logbooks; Whaling -- Peru; Whalers (Persons) -- Massachusetts -- Nantucket; Voyages to the Pacific coast